Genealogy and the Dialectics of Modernity: Tracing the Historical Roots of Nusantara Islamic Education Hybridity (17th Century to the Digital Era) - Waliya Purnama Sari; Indah Wigiati; Fajri Ismail; Yuniar Yuniar (al-Afkar, Journal For Islamic Studies, 2026)
This article analyzes the genealogy and dialectics of modernity as a strategic foundation for the transformation of Islamic education in Nusantara from the 17th century to the digital era. The study aims to dissect the consciousness structure behind the evolution of Islamic educational institutions as they transition from traditional entities to contemporary hybrid models. Using a qualitative design with a historical-phenomenological approach, this analysis traces the historical trajectory starting from the Jawi-Haramain transnational networks, the pesantren system, to the dialectical responses against colonialism and digital disruption. Research findings indicate that Islamic education in Indonesia has successfully constructed a 'third space' through 'genius acculturation,' shielding the institution from the dichotomy of secularism and extreme conservatism. The dialectics between tradition and modernity have produced competitive hybrid typologies that are now evolving into digital ecosystems. The study concludes that the transformative power of Nusantara Islamic education lies in its resilience in reconciling divine authority with technological literacy, offering a prototype for future Islamic education that is resilient to global disruption without losing its spiritual identity.